2021
DOI: 10.3389/fmolb.2021.742859
|View full text |Cite
|
Sign up to set email alerts
|

1H -NMR Metabolomics Study of the Effect of Cisplatin and Casiopeina IIgly on MDA-MB-231 Breast Tumor Cells

Abstract: The knowledge of the metabolic processes of designed metallodrugs for cancer treatment is an area that has been not profoundly studied. Casiopeina IIgly (CasIIgly), which belongs to the Casiopeínas® family, is a copper (II) coordination compound that has shown good biological activity against several cancer cells, low toxicity in normal cells, and antineoplastic activity in in vivo murine and xenografted models. In this work we employed a triple-negative highly metastatic breast carcinoma line (MDA-MB-231), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…These complexes have been extensively studied on both in vitro and in vivo models, showing that their anticancer activity is exerted through ROS accumulation that causes mitochondrial dysfunction, DNA damage and induces apoptosis [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Some of these derivatives have been selected as candidates for Phase I clinical trials [ 48 , 49 , 50 ].…”
Section: Mixed Cu(ii) Phen-based Complexesmentioning
confidence: 99%
“…These complexes have been extensively studied on both in vitro and in vivo models, showing that their anticancer activity is exerted through ROS accumulation that causes mitochondrial dysfunction, DNA damage and induces apoptosis [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Some of these derivatives have been selected as candidates for Phase I clinical trials [ 48 , 49 , 50 ].…”
Section: Mixed Cu(ii) Phen-based Complexesmentioning
confidence: 99%
“…Untargeted nuclear magnetic resonance (NMR) metabolomics has been applied to evaluate the metabolic impact of cDDP on several cancer cell lines, namely lung [19][20][21], brain [22][23][24], breast [25][26][27][28], ovarian [29] and OS [16,17,30,31]. Some of these studies analyzed whole or lysed cells, while others have focused on cellular extracts [18,23,24,28,29] and media [29]. As for OXA, to the best of the authors' knowledge, it has been assessed by NMR metabolomics of hydrophilic extracts of hepatocellular carcinoma [32] and OS [17] cells.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Several studies in the literature already exploited NMR metabolomics to evaluate the metabolic responses of cancer cells to metal based drugs, in particular Pt drugs. The effects of Cisplatin were studied in a variety of cancer cells including lung, 17 brain, [18][19][20] breast, 21,22 ovarian, 23,24 cancer cells, as well as osteosarcoma, 25,26 mostly by analyzing whole or lysed cells or focusing on cell extracts and cell media. Those studies revealed some common trends in the induced metabolic changes such as a direct effect on lipid metabolism and membrane integrity, a decrease of the overall metabolic activities of the treated cells, and the alteration of some other diagnostic metabolites e.g., UDP sugars.…”
Section: Introductionmentioning
confidence: 99%